Keunggulan Kompetitif Berbasis Value Creation pada UD. Indo Pelangi Steel di Jember - Ni Made Tina Oshadi Parwati (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This research aims to analyze value creation in enhancing competitive advantage at UD. Indo Pelangi Steel Jember. This research employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation. Informants consisted of the owner, employees, and customers selected using purposive sampling. Data were analyzed using domain and taxonomic analysis, while data validity was ensured through source triangulation. The results show that value creation at UD. Indo Pelangi Steel is implemented through four main aspects: efficiency, quality, innovation, and customer responsiveness. Efficiency is reflected in the optimization of resources and production processes. Quality is maintained through production control and selective raw material usage. Innovation is demonstrated through product development, the use of production technology, and the implementation of an application-based administrative system. Customer responsiveness is shown through product customization and prompt handling of customer complaints. These aspects collectively contribute to strengthening the company's competitive advantage. This research concludes that competitive advantage at UD. Indo Pelangi Steel is built through the integration of efficiency, quality, innovation, and customer responsiveness, supported by practical experience, continuous learning, and adaptability to market needs
Finalisasi 14 Juli 2026_Yudi
Keywords: Value Creation; Competitive Advantage; MSMEs; Manufacturing Industry